Dual‐channel capsule generation adversarial network based blockchain technology for a secured dynamic optimal routing in mobile ad hoc network. Issue 2 (8th December 2022) - M, Vanitha; Anand, Sujatha Jamuna; V, Radhamani; Rajalakshmi, N. R.
Abstract: Mobile ad hoc network (MANET) routing is allocated packets to the base station. It preserves the routing buttressing and the efficiency of MANET. None of effective approaches presented so far averting spiteful node occurrences. To overcome this issue, in this article, dual‐channel capsule generation adversarial network (DCCGAN) optimized with arithmetic optimization algorithm is proposed for blockchain based trusted distributed routing scheme in MANET (DCCGAN‐AOA‐BC‐MANET). The proposed approach offers the distributed trust module for routing nodes in MANETs that is proof‐of‐authority through blockchain. Here, the token is engendered for the packet stream admittances with the secret key transmitted to every routing mobile node, also it offers the optimum path for data transmission. The trusted distributed optimum routing information is distributed based upon proposed blockchain based MANET. The proposed approach is simulated utilizing NS‐3 tool. The performance metrics, such as delay performance, average delay, average latency, average energy consume, BC token transactions throughput. The simulation of proposed DCCGAN‐AOA‐BC‐MANET method provides 76.26%, 65.57%, 80.32%, and 42.9% lower transaction latency, 73.06%, 63.82%, 85.56%, and 38.84% lower energy consumption compared to the existing methods. Abstract : In this article, dual‐channel capsule generation adversarial network (DCCGAN) optimized with arithmetic optimization algorithm is proposed for blockchain based trusted distributed routing scheme in MANET (DCCGAN‐AOA‐BC‐MANET). The proposed approach offers the distributed trust module for routing nodes in MANETs that is proof‐of‐authority through blockchain.